2020
DOI: 10.35784/bud-arch.802
|View full text |Cite
|
Sign up to set email alerts
|

Liquid plastic films as a solution in terms of tightness problems and roofs aesthetics improvement – review

Abstract: Liquid plastic films are understood as single- or two- or multi-component polymer or polymer bitumen mixtures. Liquid plastic films must meet the requirements for waterproofing insulation, which means, among others, that they must protect the roof from mechanical damage and have resistance to weather conditions. Suitability for use as waterproofing must be confirmed by an ETA (European Technical Assessment) certificate. The article presents the advantages and disadvantages of waterproofing coatings. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Meanwhile, Ksit and Plich [51] presented liquid-plastic films as a waterproofing solution composed of a mixture of polymers or polymers and bitumen. These authors' studies demonstrated that using these plastic films could provide a smooth and uniform surface, resulting in an excellent aesthetic result and even a "cool roof," capable of reducing the greenhouse effect in large cities.…”
Section: Review and Discussion Of The Selected Papersmentioning
confidence: 99%
“…Meanwhile, Ksit and Plich [51] presented liquid-plastic films as a waterproofing solution composed of a mixture of polymers or polymers and bitumen. These authors' studies demonstrated that using these plastic films could provide a smooth and uniform surface, resulting in an excellent aesthetic result and even a "cool roof," capable of reducing the greenhouse effect in large cities.…”
Section: Review and Discussion Of The Selected Papersmentioning
confidence: 99%
“…Meanwhile, Ksit and Plich [44] presented liquid plastic films as a waterproofing solution composed of a mixture of polymers or polymers and bitumen. These authorsʹ studies demonstrated that using these plastic films could provide a smooth and uniform surface, resulting in an excellent aesthetic result and even a ʺcool roof,ʺ capable of reducing the greenhouse effect in large cities.…”
Section: The State-of-the-artmentioning
confidence: 99%
“…Roofing membranes may play the role of either an airtight ("housewrap") or waterproofing layer [12]. The nomenclature used in relation to different types of roofing membranes can be misleading to people lacking adequate knowledge.…”
Section: Types Of Roofing Membranesmentioning
confidence: 99%